Dynamic Analysis of the Fruit Sugar-Acid Profile in a Fresh-Sweet Mutant and Wild Type in ‘Shatangju’ (Citrus reticulata cv.) - Xiangyang Li; Yuan Zeng; Ting Wang; Bo Jiang; Mingjing Liao; Yuanda Lv; Juan Li; Yun Zhong (Plants, 2024)
Citrate is a major determinant of fruit flavor quality. Currently, citrus species and/or varieties with significant alterations in citrate level have greatly advanced the molecular basis of citrate accumulation in fruit. However, in-depth dissections of the molecular mechanism specific to citrate accumulation are still limited due to the lack of mutants, especially within one single variety. In this study, a fresh-sweet ‘Shatangju’ mutant (Citrus reticulata cv.) was obtained during a survey of citrus resources in Guangdong, China, and the phenotype, fruit morphology, and primary flavor profiles were comparatively analyzed. Unlike the wild-type ‘Shatangju’ (WT), the mutant (MT) material exhibited a dwarfed and multi-branched tree shape, delayed flowering and fruit ripening at maturity, a prolonged fruit tree-retention time, and a decreased single fruit weight at maturity. Dynamic measurement of the metabolite levels further suggested that the contents and fluctuation patterns of vitamin C, malate, quinate, and oxalate showed no obvious difference between MT and MT fruits, while the citrate level in MT fruits significantly decreased over various developmental stages, ranging from 0.356 to 1.91 mg g−1 FW. In addition, the accumulation patterns of the major soluble sugars (sucrose, fructose, and glucose), as well as the sugar/acid ratio, were also altered in MT fruits during development. Taken together, this study provides a novel acid-free ‘Shatangju’ mutant, which can serve as a powerful tool for the research of fruit flavor quality, especially for the comprehensive understanding of the molecular mechanism of citrate accumulation in fruits.